2016
DOI: 10.18632/oncotarget.7755
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic roles of TOPK and MELK, and effective growth suppression by small molecular inhibitors in kidney cancer cells

Abstract: T–lymphokine-activated killer cell–originated protein kinase (TOPK) and maternal embryonic leucine zipper kinase (MELK) have been reported to play critical roles in cancer cell proliferation and maintenance of stemness. In this study, we investigated possible roles of TOPK and MELK in kidney cancer cells and found their growth promotive effect as well as some feedback mechanism between these two molecules. Interestingly, the blockade of either of these two kinases effectively caused downregulation of forkhead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 31 publications
3
71
1
1
Order By: Relevance
“…Our previous studies showed that inhibition of TOPK kinase activity reduced stability of 2 5 TOPK protein itself through the downregulation of autophosphorylation and resulted in reduction of FOXM1 transcriptional level (11,18). Similarly in ES-2 and SKOV3 ovarian cancer cell lines, we found that TOPK inhibitors reduced TOPK protein level and suppressed transcription of FOXM1, which probably led to the growth inhibition of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our previous studies showed that inhibition of TOPK kinase activity reduced stability of 2 5 TOPK protein itself through the downregulation of autophosphorylation and resulted in reduction of FOXM1 transcriptional level (11,18). Similarly in ES-2 and SKOV3 ovarian cancer cell lines, we found that TOPK inhibitors reduced TOPK protein level and suppressed transcription of FOXM1, which probably led to the growth inhibition of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 57%
“…Expression levels of TOPK protein and FOXM1 mRNA were examined by western blot and RT-PCR, respectively, as described previously (17,18). …”
Section: Western Blotting and Rt-pcrmentioning
confidence: 99%
“…4,5 Maternal embryonic leucine zipper kinase (MELK) is a member of the AMP protein kinase (AMPK) family of serine/threonine kinases, and MELK activates multiple cellular pathways that drive oncogenic growth. [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL). [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL).…”
Section: Introductionmentioning
confidence: 99%
“…23 High levels of MELK are correlated with clinically aggressive disease and poor survival. 19,[22][23][24][25] A number of studies have shown that MELK inhibition also increases sensitivity to radiation and chemotherapy in pre-clinical adult cancer models, suggesting that combination treatments may also be effective strategies. 19,[22][23][24][25] A number of studies have shown that MELK inhibition also increases sensitivity to radiation and chemotherapy in pre-clinical adult cancer models, suggesting that combination treatments may also be effective strategies.…”
Section: Introductionmentioning
confidence: 99%
“…MELK is highly overexpressed in several cancer types and its inhibition has been shown to block the tumor growth of some cancers (Inoue et al, 2016; Joshi et al, 2013; Kato et al, 2016; Wang et al, 2016; Wang et al, 2014). Interestingly, MELK knockout mice are viable and do not show any specific phenotypes (Wang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%